The Analyse of Concept Understanding of 5th Grade Elementary School Student towards Air in Science Subjects by Using Blended Learning - Suryana, Sabila Idzni; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The aim of this research is to see science concept understanding of 5th grade Elementary School students towards learning material about air through Blended Learning model. This research uses qualitative descriptive method that involved 20 Elementary School students in grade 5 at a school in Sumedang Regency, West Java Province. The data collection was conducted by using instruments in the form of essay test questions to measure the students’ science concept understanding towards aspects of factual, conceptual, and metacognitive knowledge that were collected through google form. The results show that the students’ understanding about air material towards factual aspect enters high category with a percentage of 76.7%, towards conceptual aspect enters middle category with a percentage of 74.1%, and towards metacognitive aspect enters middle category with a percentage of 61.8%. Therefore, it is proved that students’ science concept understanding towards air material by using Blended Learning model is good enough. This happened because Blended Learning model can make students capable to follow the learning activity well that is shown by the good learning results and their activeness during learning activity in the class. However, to maximize the implementation of this learning model, the combination between Blended learning with another learning model is needed.